Učinkovitost kognitivnega treninga z zbirko Misleca pri otrocih v srednjem otroštvu - Strojnik, Zala (Psihološka obzorja (Ljubljana), 2021)
Studies on the effectiveness of cognitive training do not show consistent results. While some have shown positive effects of the training on fluid intelligence and other cognitive abilities, others have not. Studies of the effectiveness of cognitive training in normative middle childhood children and studies on multicomponent cognitive training are rare. The aim of our study was to investigate the effect of cognitive training in the form of regular solving of mental tasks from the 'Misleca' manual on cognitive abilities in middle childhood. Thirty-eight children with a mean age of 8 years 5 months (SD = 3 months) were randomly divided into two halves, forming an experimental and a control group. After the pre-tests to measure fluid intelligence, verbal fluency, working memory, switching ability, inhibition and visuo-spatial planning, the experimental group participated in the training, which was conducted three times a week over a period of six weeks. After each session the children reported on their motivation for the training. The control group was passive. After six weeks, cognitive tests were carried out again. The results showed a positive eff ect of the training on the Raven's Coloured Progressive Matrices score as a measure of fluid intelligence, while no effect on other cognitive abilities was observed. The results also showed that the children found the training interesting and that the majority were motivated to solve the tasks.
Keywords: Barvne progresivne matrice; brain training; children; cognitive ability; cognitive processes; cognitive psychology; Coloured progressive matrices; executive function; fluid intelligence; fluidna inteligentnost; izvršilne funkcije; kognitivna psihologija; kognitivni procesi; kognitivni trening; middle childhood; otroci; spoznavne sposobnosti; srednje otroštvo; Test sledenja TMT; Test verbalne fluentnosti; Testna baterija za merjenje izvršilnih funkcij; Trail-making test TMT